The Latino male : a radical redefinition - Abalos, David T. (Lynne Rienner Publishers, 2002)
The author presents a critique of archetypal roles of Latino males including the womanizer, the macho, and the patriarch. As an alternative to these outdated and restrictive ways of living, he describes how Latino males are able to radically redefine themselves and create new transformational archetypes. He goes on to discuss how Latino men can become agents of transformation in the family and the larger world.